2019
DOI: 10.24191/jibe.v4i2.14310
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Social Responsibility towards Consumer Buying Behaviour: A Study among Universities Students

Abstract: Business corporations need to realize that in order to achieve their primary objective, they need to consider their responsibility towards society and environment. However, there are still a lot of unethical businesses that ignore their stakeholder’s interest. Therefore, business need to aware that their involvement of CSR practices in certain extent does affect the consumer buying behavior. This paper examines the relationship between CSR practices and consumer buying behavior. Quantitative approach was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Nevertheless, contrary findings were discovered in another study. Thomas & Tahir (2019) found that, compared to other perspectives of CSR, the economic element in CSR had the strongest and most significant relationship with consumer purchasing behaviour. The findings are consistent with the findings of Safi and Ramay (2013), who discovered that economic responsibilities are the most important for organisations.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Nevertheless, contrary findings were discovered in another study. Thomas & Tahir (2019) found that, compared to other perspectives of CSR, the economic element in CSR had the strongest and most significant relationship with consumer purchasing behaviour. The findings are consistent with the findings of Safi and Ramay (2013), who discovered that economic responsibilities are the most important for organisations.…”
Section: Introductionmentioning
confidence: 88%
“…The study took place in a public university in Selangor, Malaysia's largest economy with a conducive business environment that is home to numerous business organisations. The university students were chosen as the respondents to represent consumers (Thomas and Tahir, 2019;Tan and Komaran, 2006). Systematic sampling method was used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations